2011
DOI: 10.1590/s0103-50532011000600012
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electrochemical microscopy: study of the deposition and stripping mechanism of lead in the presence of copper

Abstract: Este artigo descreve a utilização da microscopia eletroquímica de varredura (SECM) no modo geração pelo substrato/coleta pela ponta (SG/TC), com o objetivo de elucidar aspectos mecanísticos da deposição eletrolítica e redissolução anódica de íons Pb 2+ na presença de Cu 2+, utilizando-se um eletrodo de carbono vítreo como substrato. Um pico anódico foi observado entre os principais picos correspondentes à redissolução dos metais puros. A posição, intensidade e forma deste pico foram investigadas e foi verifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Due to the difference in electrodeposition potentials between Cu II , Pb II , and Cd II , electrodeposition at varying potentials was carried out from a mixed Cu II , Pb II , and Cd II solution for 200 s. It is predicted that Cu II can be recovered alone at potentials < −0.65 V vs AgCl|Ag, evidenced by a single anodic stripping peak in the voltammogram shown in Figure 5 d. At–0.70 and −0.90 V vs AgCl|Ag, Pb–Cu alloys were deposited. Three anodic stripping peaks are observed, where peak 1 is associated with Cu stripping, while peaks 2 and 3 are associated with stripping of Pb deposited from glassy carbon and copper, respectively, 66 as previously reported. At −1.10 V deposition, an additional peak 4 was evident due to prior electrodeposition of an Cd–Pb–Cu alloy.…”
Section: Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Due to the difference in electrodeposition potentials between Cu II , Pb II , and Cd II , electrodeposition at varying potentials was carried out from a mixed Cu II , Pb II , and Cd II solution for 200 s. It is predicted that Cu II can be recovered alone at potentials < −0.65 V vs AgCl|Ag, evidenced by a single anodic stripping peak in the voltammogram shown in Figure 5 d. At–0.70 and −0.90 V vs AgCl|Ag, Pb–Cu alloys were deposited. Three anodic stripping peaks are observed, where peak 1 is associated with Cu stripping, while peaks 2 and 3 are associated with stripping of Pb deposited from glassy carbon and copper, respectively, 66 as previously reported. At −1.10 V deposition, an additional peak 4 was evident due to prior electrodeposition of an Cd–Pb–Cu alloy.…”
Section: Results and Discussionsupporting
confidence: 83%
“…At–0.70 and −0.90 V vs AgCl|Ag, Pb–Cu alloys were deposited. Three anodic stripping peaks are observed, where peak 1 is associated with Cu stripping, while peaks 2 and 3 are associated with stripping of Pb deposited from glassy carbon and copper, respectively, as previously reported. At −1.10 V deposition, an additional peak 4 was evident due to prior electrodeposition of an Cd–Pb–Cu alloy.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some authors also observed secondary anodic stripping voltammetric peaks when lead was electrodeposited in the presence of copper on glassy carbon electrodes. 43 These secondary peaks were observed between the main peaks of pure metals and they were attributed to the anodic stripping of deposited lead on copper. 43 SiAt-SPCPE also present another anodic peak at +0.33 V which was already detected in cyclic voltammetric studies (Figure 1 inset).…”
Section: Preliminary Studiesmentioning
confidence: 98%
“…43 These secondary peaks were observed between the main peaks of pure metals and they were attributed to the anodic stripping of deposited lead on copper. 43 SiAt-SPCPE also present another anodic peak at +0.33 V which was already detected in cyclic voltammetric studies (Figure 1 inset). This voltammetric peak is probably attributed to an oxidation process of 2-aminothiazole since it is absent at SPCPE.…”
Section: Preliminary Studiesmentioning
confidence: 98%